After Pevsner: Problems of the new design history - Kaizer, Felipe (Arcos Design, 2023)
This article analyses core issues of the histories of design brought to light after the pioneering work of Nikolaus Pevsner. Among these, economic and materialistic assumptions of social design history stand out, as does the dispute between different approaches within world history of design or global design history. The article investigates the main characteristics of Pevsner’s work, the proposal and the analysis made by Clive Dilnot's of a new design history and of the post-development of such research.